what is the answer to the equation -6x-7=-1(-9+2x)

Question

what is the answer to the equation -6x-7=-1(-9+2x)

in progress 0
Parker 1 week 2021-10-12T13:10:10+00:00 1 Answer 0

Answers ( )

    0
    2021-10-12T13:11:25+00:00

    Answer:

    This is easy

    so first your want to distribute the -1 to everything in the parenthesis

    making the equation -6x-7=9-2x

    then you solve for x (thinking that you know how to do that

    -4x=16

    then divide by -4

    x=-4

    Step-by-step explanation:

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )